Identifying Putative Drug Target in Methicillin Resistant Staphylococcus aureus Using in silico Proteome Subtraction Analysis - Vu, Le Anh; Quyen, Phan Thi Cam; Huong, Nguyen Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 1DO - 10.25073/2588-1140/vnunst.4813, 2019)
This paper analyzes the proteomes of 15 different MRSA strains using an in silico subtraction approach to identify putative drug targets. Various bioinformatics tools were used to screen for paralogous sequences and homologous proteins against the host ( Homo sapiens ) from the bacterial proteome. The remaining proteins were further analyzed to identify essential proteins using the Database of Essential Genes (DEG). The results show that 2,235 proteins in MRSA were not homologous with the host proteome, and 158 of these proteins were identified as the essential proteins for the viability of S. aureus according to DEG. Moreover, metabolic pathway analysis of essential proteins with the Kyoto Encyclopedia of Genes and Genomes (KEGG) verified that 49 proteins participated in 11 unique metabolic pathways in MRSA. The identified proteins are expected to have great potential in drug design against MRSA. Keywords Drug targets, essential proteins, human non-homologous, MRSA, proteome subtraction. References [1] S.J. Peacock, G.K. Paterson, Mechanisms of methicillin resistance in Staphylococcus aureus, Annu. Rev. Biochem. 84(1) (2015) 577-601. [2] F.D. Lowy, Antimicrobial resistance: the example of Staphylococcus aureus, J. Clin. Invest. 111(9) (2003) 1265-1273. [3] P.D. Stapleton, P.W. Taylor, Methicillin resistance in Staphylococcus aureus: mechanisms and modulation, Sci. Prog. 85(1) (2002) 57-72. [4] R. Uddin, K. Saeed, Identification and characterization of potential drug targets by subtractive genome analyses of methicillin resistant Staphylococcus aureus, Comput. Biol. Chem. 48 (2014) 55-63. [5] T. Hossain, M. Kamruzzaman, T.Z. Choudhury, H.N. Mahmood, A.H.M.N. Nabi, Md.I. Hosen, Application of the subtractive genomics and molecular docking analysis for the identification of novel putative drug targets against Salmonella enterica subsp. Enterica serovar poona, BioMed Res. Int. Vol. 2017 (2017) Article ID 3783714, 9 pages. [6] N. Haag, K. Velk, C. Wu, In silico identification of drug targets in methicillin/multidrug-resistant Staphylococcus aureus, In: BIOTECHNO 2011, The Third International Conference on Bioinformatics, Biocomputational Systems and Biotechnologies, IARIA, Nice, 2011, pp. 91-99. [7] M. Hossain, D.U.S Chowdhury, J. Farhana, M.T. Akbar, A. Chakraborty, S. Islam, A. Mannan, Identification of potential targets in Staphylococcus aureus N315 using computer aided protein data analysis, Bioinformation. 9(4) (2013) 187-192. [8] S. Pundir, M.J. Martin, C. O’Donovan, Chapter 2. Protein Knowledgebase, Methods Mol. Biol. 1558 (2017) 41-55. [9] R.C. Edgar, Search and clustering orders of magnitude faster than BLAST, Bioinformatics. 26(19) (2010) 2460-2461. [10] M.A Hasan, S.M. Alauddin, M. Al-Amin, S.M. Nur, A. Mannan, Identification of putative drug targets in vancomycin-resistant Staphylococcus aureus (VRSA) using computer aided protein data analysis, Gene. 575(1) (2016) 132-143. [11] T. UniProt Consortium, UniProt: the universal protein knowledgebase, Nucleic Acids Res. 46(5) (2018) 2699. [12] A. Gautam, R. Vyas, R. Tewari, Peptidoglycan biosynthesis machinery: A rich source of drug targets, Crit. Rev. Biotechnol. 31(4) (2011) 295-336. [13] C.K. Teo, D.I. Roper, Core steps of membrane-bound peptidoglycan biosynthesis: recent advances, insight and opportunities, Antibiotics. 4(4) (2015) 495-520. [14] Y. Liu, E. Breukink, The membrane steps of bacterial cell wall synthesis as antibiotic targets, Antibiotics. 5(3) (2016) 28. [15] A. Kovač, J. Konc, B. Vehar, J.M. Bostock, I. Chopra, D. Janežič, S. Gobec, Discovery of new inhibitors of d-alanine:d-alanine ligase by structure-based virtual screening, J. Med. Chem. 51(23) (2008) 7442-7448. [16] I. Tytgat, E. Colacino, P.M. Tulkens, J.H. Poupaert, M. Prevost, F. Van Bambeke, DD-ligases as a potential target for antibiotics: past, present and future, Curr. Med. Chem. 16(20) (2009) 2566-2580. [17] J. Deutscher, C. Francke, P.W. Postma, How phosphotransferase system-related protein phosphorylation regulates carbohydrate metabolism in bacteria, Microbiol. Mol. Biol. Rev. 70(4) (2006) 939-1031. [18] J. Deutscher, F.M.D. Aké, M. Derkaoui, A. C. Zébré, T.N. Cao, H. Bouraoui, T. Kentache, A. Mokhtari, E. Milohanic, P. Joyet, The bacterial phosphoenolpyruvate:carbohydrate phosphotransferase system: regulation by protein phosphorylation and phosphorylation-dependent protein-protein interactions, Microbiol. Mol. Biol. Rev. 78(2) (2014) 231-256. [19] F.C. Fang, E.R. Frawley, T. Tapscott, A. Vazquez-Torres, Bacterial stress responses during host infection, Cell Host Microbe. 20(2) (2016) 133-143. [20] G. Renzone, C. D'Ambrosio, S. Arena, R. Rullo, L. Ledda, L. Ferrara, A. Scaloni, Differential proteomic analysis in the study of prokaryotes stress resistance, Ann Ist Super Sanita 41(4) (2005) 459-468. [21] G. Storz, R. Hengge-Aronis, Bacterial stress responses, ASM Press, Washington DC, 2000. [22] R.A. VanBogelen, K.D. Greis, M. Blumenthal, T.H. Tani, R. Matthews, Mapping regulatory networks in microbial cells, Trends Microbiol. 7(8) (1999) 320-328. [23] E. Bem, N. Velikova, M.T. Pellicer, P. van Baarlen, A. Marina, J.M. Wells, Bacterial histidine kinases as novel antibacterial drug targets, ACS Chem. Biol. 10(1) (2015) 213-224. [24] S. Wang, Bacterial two-component systems: structures and signaling mechanisms, In C. Huang (Eds.), Protein Phosphorylation in Human Health, IntechOpen, London, 2012, pp. 439-466. [25] S. Tiwari, S.B. Jamal, S.S. Hassan, P.V.S.D. Carvalho, S. Almeida, D. Barh, P. Ghosh, A. Silva, T.L.P Castro, V. Azevedo, Two-component signal transduction systems of pathogenic bacteria as targets for antimicrobial therapy: an overview, Front. Microbiol. 8 (2017) 1878. [26] S.T. Rutherford, B.L. Bassler, Bacterial quorum sensing: its role in virulence and possibilities for its control, Cold Spring Harb. Perspect. Med. 2(11) (2012) a012427. [27] J. Park, R. Jagasia, G.F. Kaufmann, J.C. Mathison, D.I. Ruiz, J.A. Moss, M.M Meijler, R.J. Ulevitch, K.D. Janda, Infection control by antibody disruption of bacterial quorum sensing signaling, Chem. Biol. 14 (2007) 1119-1127. [28] M. Otto, Virulence factors of the coagulase-negative staphylococci, Front. Biosci. 9 (2004) 841-863. [29] R.M. Braga, M.N. Dourado, W.L. Araújo, Microbial interactions: ecology in a molecular perspective, Braz. J. Microbiol. 47(Suppl 1) (2016) 86-98. [30] L. Demain, A. Fang, The natural functions of secondary metabolites, Adv. Biochem. Eng. Biotechnol. 69 (2000) 1-39. [31] H. Nikaido, Multidrug resistance in bacteria, Annu. Rev. Biochem. 78 (2009) 119-146. [32] E.R. Green, J. Mecsas, Bacterial secretion systems – an overview, Microbiol. Spectr. 4(1) (2016) 10.1128/microbiolspec.VMBF–0012–2015. [33] E.G. Parizad, E.G. Parizad, I. Pakzad, A. Valizadeh, A review of secretion systems in pathogenic and non-pathogenic bacteria, Biosci. Biotech. Res. Asia. 13(1) (2016) 135-145. [34] A. Srinivasan, J.D. Dick, T.M. Perl, Vancomycin resistance in Staphylococci, Clin. Microbiol. Rev. 15(3) (2002) 430-438. [35] S. Gardete, A. Tomasz, Mechanisms of vancomycin resistance in Staphylococcus aureus, J. Clin. Invest. 124(7) (2014) 2836-2840. [36] W.A. McGuinness, N. Malachowa, F.R. DeLeo, Vancomycin resistance in Staphylococcus aureus, Yale J. Biol. Med. 90(2) (2017) 269-281.